Social Studies Learning with Numbered Head Together Model Improves Learning Outcomes Viewed from Student Learning Motivation - Wati, Ni Komang Sri; Suarni, Ni Ketut (Universitas Pendidikan Ganesha, 2020)
The lack of optimal learning outcomes of social studies for fifth-grade elementary school students in Cluster XI Buleleng District is the main reason for this research. This study aims to analyze the effect of numbered head together (NHT) learning models, assisted by audio-visual media on social studies learning outcomes in terms of the learning motivation of fifth-grade elementary school students. Types of this research is a quasi-experiment with a non-equivalent post-test only control group design. The population in this study was grade V elementary school. The sample in this study was the VB class at SD Singaraja Lab of 35 students and VA class at SD Lab Singaraja of 35 students. Data collection methods used were of multiple-choice tests and non-test methods in the form of questionnaires. Learning outcomes data obtained were analyzed using Anava two pathways. The results showed that there were differences in social studies learning outcomes between students who were taught with the NHT model assisted by audiovisual media and students who were taught conventional learning models, there was an interaction effect between the learning model of NHT assisted with audiovisual media with learning motivation towards students' social studies learning outcomes, there was the difference in social studies learning outcomes between students who are taught with the NHT model assisted by audio-visual media and students who were taught conventional learning models to students who have high learning motivation, there was the difference in social studies learning outcomes between students who are taught with the NHT model assisted by audio-visual media and students who were taught conventional learning models to students who have low learning motivation. Based on the results of the study it can be concluded that the numbered head together learning model assisted by audiovisual media has a positive effect on social studies learning outcomes in terms of the learning motivation of students.